Korean teachers' and learners' perceptions of world Englishes - Chang, Kum Young (2019)
As English has been more and more used all around the world, there has been calling for more inclusion of World Englishes (WEs) in English education. English education in Korea, however, still centers on native speaker models, relatively little research investigating WEs from teachers’ and students’ perspectives. The purpose of this study is, therefore, to explore Korean teachers’ and learners’ perceptions of WEs, building on previous work on WEs. Questionnaires, which included both close-ended and open-ended questions, were designed and given to 51 teachers and 79 students in Korea, together with sample speeches representing different WEs. The questions asked participants’ understanding of WEs, English varieties they had learned, taught, and been exposed to, and their attitudes towards including diverse WEs in English education. The results indicated that the participants, in general, had some knowledge of WEs, had mostly learned, taught, and been exposed to American English, and were positive about incorporating varying WEs in English education although some of them were rather skeptical of the inclusion. Comparing the two groups, the teachers showed a better understanding of WEs, and they were more open to the inclusion. The study concludes that English education in Korea needs to be changed into teaching/learning English as a practical language, and diversify the language, reflecting voices from teachers and students. It also suggests that information on WEs which is widely shared by research literature should also be shared with teachers and students before they make any educational choice regarding WEs.